The packaging designer's book of patterns. - Wybenga, George L., ....-; Roth, Laszlo, ....- (Hoboken : Wiley, 2006)
Today packaging design is increasingly integral to product development activities and is among the earliest considerations of product designers and brand managers. The new edition of this unparalleled practical resource offers the tools necessary to create innovative, cost-effective packaging with over 500 packaging patterns drawn to scale and ready to use by designers and packaging professionals.
Keywords: Verpakkingen